Variations of Organic Fertilizer Dose to The Three Varieties of Sweet Sorghum Growth and Yield for Bioethanol - Nurngaini Nurngaini; Rati Riyati (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2016)
Field experiments to study